Investigating age at onset in bipolar disorder - Bolton, S (2023)
Bipolar disorder (BD) is a complex mental health disorder with a heterogenous clinical course, diagnostic delays, high relapse rates, and sub-optimal treatment outcomes. Age at onset (AAO) has been proposed as a useful specifier for defining more homogeneous BD subgroups that can inform clinical course and symptom profiles. This thesis aimed to investigate the utility of AAO as a clinical specifier by defining and validating AAO subgroups; identifying predictive factors for BD AAO; investigating the relationship between premorbid factors, AAO, and functional outcomes; and examining the association between AAO and mood instability.